Pengaruh Kepemimpinan Transformasional, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan” (Studi Pada Badan PT. Kereta Api Indonesia Daop IV Semarang) - Sri Wahyuni, 14.05.51.0155; Indriyaningrum, Kis (Students' Journal of Economic and Management, 2019)
This study examines the effect of transformational leadership, work motivation, work environment and employee performance. This research was conducted at PT KAI DAOP IV Semarang. The sampling method uses purposive sampling with a period of 2013. The relationship and / or influence between variables is explained using multiple regression analysis methods. The results showed that transformational leadership, work motivation and work environment had a significant positive effect on employee performance in the company.